Evaluation of wild edible mushrooms in Vansda National Park, Gujarat, India - Patel, Jigitsa; Patel, Dilipkumar; Patel, Dhruv (Current Botany, 2025)
The Vansda National Park is situated in Navsari in South Gujarat on the northern-most limit of the Western Ghats. This park is famous for the biodiversity of flora and fauna. The area is also quite rich in mushrooms, many of which are traditionally used by local communities for food and medicine due to their palatability, nutritional, and nutraceutical attributes. The area under investigation was unexplored, as far as mushroom biodiversity is concerned because for which this study was undertaken. The study aimed to gather information about the wild edible mushrooms growing in Vansda National Park with a view to familiarizing about their ethnic uses, including their respective local names and cooking methods. During the survey, as many as 100 respondents were consulted who revealed the edibility of 21 mushroom species by the locals by preparing various preparations, including soup, and other dishes.